Glu-ureido-based inhibitors of prostate-specific membrane antigen: lessons learned during the development of a novel class of low-molecular-weight theranostic radiotracers - Kopka, Klaus; Haberkorn, Uwe (Journal of nuclear medicine, 2017)
In recent years, several radioligands targeting prostate-specific membrane antigen (PSMA) have been clinically introduced as a new class of theranostic radiopharmaceuticals for the treatment of prostate cancer (PC). In the second decade of the 21st century, a new era in nuclear medicine was initiated by the clinical introduction of small-molecule PSMA inhibitor radioligands, 40 y after the clinical introduction of 18F-FDG. Because of the high incidence and mortality of PC, the new PSMA radioligands have already had a remarkable impact on the clinical management of PC. For the continuing clinical development and long-term success of theranostic agents, designing modern prospective clinical trials in theranostic nuclear medicine is essential. First-in-human studies with PSMA radioligands derived from small-molecule PSMA inhibitors showed highly sensitive imaging of PSMA-positive PC by means of PET and SPECT as well as a dramatic response of metastatic castration-resistant PC after PSMA radioligand therapy. This tremendous success logically led to the initiation of prospective clinical trials with several PSMA radioligands. Meanwhile, MIP-1404, PSMA-11, 2-(3-{1-carboxy-5-[(6-fluoro-pyridine-3-carbonyl)-amino]-pentyl}-ureido)-pentanedioic acid (DCFPyL), PSMA-617, PSMA-1007, and others have entered or will enter prospective clinical trials soon in several countries. The significance becomes apparent by, for example, the considerable increase in the number of publications about PSMA-targeted PET imaging from 2013 to 2016 (e.g., a search of the Web of Science for “PSMA” AND “PET” found only 19 publications in 2013 but 218 in 2016). Closer examination of the initial success of PC treatment with PSMA inhibitor radiotracers leads to several questions from the basic research perspective as well as from the perspective of clinical demands: What lessons have been learned regarding the design of PSMA radioligands that have already been developed? Has an acceptable compromise between optimal PSMA radioligand design and a broad range of clinical demands been reached? Can the lessons learned from multiple successes within the PSMA experience be transferred to further theranostic approaches?
Gesehen am 15.11.2018